KARAKTERISTIK MINUMAN FUNGSIONAL EKSTRAK DAUN KERSEN ( Mutingia calabura L.) DAN MADU - Nopi Sri Wahyunita; Ika Gusriani; Silvi Leila Rahmi (Universitas Wahid Hasyim, 2023)
CherryÂ leaf is a leaf with strong antioxidant activity, so it is suitable for use as a functional drink. Functional drinks are drinks that have health functions, made from natural ingredients and are safe for daily consumption. This research was conducted with the aim to determine effect of the comparison of honey and cherry leaf extract (Muntingia calabura L.) on the characteristics of the functional drinks produced, as well as to determine the right formulation for the characteristics of cherry leaf extract functional drinks with the addition of honey. Parameters observed were antioxidant activity test, total dissolved solids analysis, Color Reader color analysis, degree of acidity, and organoleptic test. The results of the comparison of honey and cherry leaf extract had a significant effect on total dissolved solids, pH, color and organoleptic (taste, color and overall acceptability), but had no significant effect on antioxidant and organoleptic activity (scent). The best comparison formulation of honey and cherry leaf extract is 30% honey and 70% cherry leaf extract with a pH value of 3.66, total dissolved solids value of 26.93 0Brix, color description namely Yellow Red (YR), antioxidant activity of 85.93 %, aroma 3.10 (rather like), taste 4.05 (sweet), color 4.24 (brown) and overall acceptance 3.71 (like). In conclusion, cherry leaf extract functional drinks with honey are intended to increase the variety of functional drinks with high antioxidant characters that are easy to serve and ready to consume. Â Keywords: Antioxidants; cherry leaves; extract, functional drinks, honey. Â